Крассулы и содержание в них фенольных соединений - Лапшин, П.В.; Загоскина, Н.В. (Фактори експериментальної еволюції організмів, 2013)
Aims. One important area of biological research is to study the various representatives of the higher plants, including in relation to their possible use for the production of biologically active secondary metabolites. These include phenolic compounds successfully used in pharmacology and medicine. The aim of the study was to investigate the accumulation of phenolic compounds in chlorophyll-defectives and corresponding normal plants of the genus Crassula (Crassula L.). Methods. In the leaves of plants determined the content the amount of soluble phenolic compounds and flavonoids. Results. Determined that in the plant leaves of Crassula sarmentosa content of phenolic compounds and flavonoids were significantly higher than in plant leaves of Crassula ovate. Conclusions. Consider that the accumulation of these secondary metabolites is dependent on many factors, including genetic characteristics of plants.